PENGARUH PENERAPAN TEKNIK IDENTITAS KORPORAT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA N 14 PADANG - Hariyanti, Yesi; Husna, Husna; Febriana, Rina (STKIP PGRI Sumbar, 2013)
The backgrounds of this research are the less understanding of studentsâ mathematical concept are still low and the worse group learning due to the lack of cooperation among groups. The aims of research are to know the studentsâ mathematical concept understanding by applying the corporate identity technique is better than that by using the conventional learning. The type of research is an experimental research with random to subject design. Based on the analysis of data found that the two classes are normally distributed and homogeneous samples at significance levelÂ Â Î± = 0,05. Hypothesis test results obtained p - value = 0,001 is less than Î± = 0,05, the hypothesis is accepted. It can be summarized that the studentsâ mathematical concept understanding by applying the corporate identity technique is better than that by using the conventional learning in class XI IPA SMAN 14 Padang Academic Year 2012/2013.